PSYCHOLOGICAL AND SOCIAL FACTORS OF DEVIATIONS FROM SOCIAL BEHAVIORAL NORMS IN ADOLESCENT GIRLS (Multidisciplinary Journal of Science and Technology, 2026)
This article provides an in-depth analysis of the psychological and social factors influencing deviations from accepted social behavior norms among adolescent girls. It emphasizes the unique characteristics of adolescence as a critical developmental stage, including identity formation, the desire for independence, heightened emotional sensitivity, and instability. These features make adolescents particularly vulnerable to external influences and internal conflicts. The study highlights the significant role of the family environment in shaping behavior. Factors such as parenting style, emotional support, communication quality, family conflicts, and neglect are examined as key determinants that may contribute to the development of deviant behavior. A lack of warmth, inconsistent discipline, or excessive control can negatively affect an adolescent girl’s psychological well-being and behavioral choices. In addition, the influence of peer groups is explored as a powerful social factor. The need for acceptance, fear of rejection, and susceptibility to peer pressure often lead adolescent girls to conform to group norms, even when those norms encourage risky or deviant behavior. The article shows that association with negative peer groups increases the likelihood of behavioral deviations.The impact of modern media and social networks is also thoroughly discussed. Exposure to unrealistic standards, constant comparison, cyberbullying, and the promotion of harmful values can significantly affect adolescents’ self-image and emotional health. These influences may lower self-esteem and increase stress, anxiety, and dissatisfaction.